Strain rate dependence of work of fracture tests on bone and similar tissues: reflections on testing methods and mineral content effects - Currey, John D.; Brear, Kevin; Zioupos, Peter (Elsevier, 2019)
This paper is concerned with the effect of different strain rate on the Work of Fracture (Wf) of various vertebrate mineralised tissues, controlling for the effect of mineral content and Young's modulus of elasticity. Using specimens of uniform shape and size values for the Work of Fracture of specimens tested at various deformation rates, and also the energy absorbed by notched specimens in impact, are reported. The results indicated that, of those tested, for most bone specimens the Work of Fracture measurements were constant like in the case for a ‘material property’. Variations due to loading conditions (deformation rate) were small, with the exemption of antler, which is relatively poorly mineralised and in which the Work of Fracture values increased by a factor of 4 across the range from quasistatic loading to impact. The Tattersall and Tappin (1966) test has shown itself to offer some great advantages: if the quest is for a fracture toughness test for an unknown tissue it offers reliability, it is perhaps more forgiving to handling errors, it also suffers less of the influence of strain rate effects and uses relatively simple instrumentation. It is also able to demonstrate the remarkable toughness of antler bone which other more commonly used fracture toughness methods cannot do.
Keywords: Bone; Antler; Dentine; Impact; Work of fracture